Biodiversity, Distribution and Conservation of Plants and Fungi Effects of Global Warming and Environmental Stress - Kosakyan, Anush; Catana, Rodica; Biketova, Alona (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue brings together some interconnected topics related to fungi and plants such as biodiversity, taxonomy, conservation, molecular phylogeny, ecology, and plant-fungal interactions. Additionally, some applied aspects are covered, such as phytoremediation, the improvement of spinach growth by biochar and arbuscular mycorrhizal fungi, bio-friendly solutions for waste reduction, the accumulation of rare-earth elements by wild edible mushrooms, etc.